Energy gap of topological surface states in proximity to a magnetic insulator - Jiashu Wang; Tianyi Wang; Mykhaylo Ozerov; Zhan Zhang; Joaquin Bermejo-Ortiz; Seul-Ki Bac; Hoai Trinh; Maksym Zhukovskyi; Tatyana Orlova; Haile Ambaye; Jong Keum; Louis-Anne de Vaulchier; et al. (Communications Physics, 2023)
Abstract Topological surface-states can acquire an energy gap when time-reversal symmetry is broken by interfacing with a magnetic insulator. This gap has yet to be measured. Such topological-magnetic insulator heterostructures can host a quantized anomalous Hall effect and can allow the control of the magnetic state of the insulator in a spintronic device. In this work, we observe the energy gap of topological surface-states in proximity to a magnetic insulator using magnetooptical Landau level spectroscopy. We measure Pb1-xSnxSe–EuSe heterostructures grown by molecular beam epitaxy exhibiting a record mobility and low Fermi energy. Through temperature dependent measurements and theoretical calculations, we show this gap is likely due to quantum confinement and conclude that the magnetic proximity effect is weak in this system. This weakness is disadvantageous for the realization of the quantum anomalous Hall effect, but favorable for spintronic devices which require the preservation of spin-momentum locking at the Fermi level.